Determinants of neonatal sepsis among neonates in the northwest part of Ethiopia: case-control study - Mulunesh Alemu; Mulatu Ayana; Hailemariam Abiy; Biniam Minuye; Wubet Alebachew; Aklilu Endalamaw (BMC, 2019)
Abstract Background Neonatal sepsis is one of the leading causes of neonatal morbidity and mortality. Despite implementing of different preventive interventions, the burden of neonatal sepsis is reporting in different areas of Ethiopia. For further interventions, identifying its determinants is found to be crucial. Objective This study aimed to identify determinants of neonatal sepsis in the Northwest part of Ethiopia. Methods Unmatched case-control study was conducted among 246 neonates admitted in neonatal intensive care unit, Northwest Ethiopia. Study participants were selected from February 1st to March 30th 2018. Data was collected through face to face interview and review of neonates' medical records using pretested structured questionnaire. Data was entered into Epi Data version 4.2.0.0 and further transferred to SPSS statistical software version 25 for analysis. All independent variables with p-value < 0.25 in Bivariable analysis were entered into multivariable logistic regression analysis. Finally, variables with p-value < 0.05 were considered as determinants of neonatal sepsis. Results A total of 82 cases and 164 controls were included in this study. Neonates with gestational age < 37 weeks [AOR = 6.90; 95% CI (2.76, 17.28)], premature rupture of membrane [AOR = 2.81; 95% CI (1.01, 7.79)], not crying immediately at birth and have received resuscitation at birth [AOR = 2.85; 95% CI (1.09, 7.47)] were found to be predictors of neonatal sepsis. Conclusions and recommendations Premature rupture of membrane was found to be obstetric-related determinant of neonatal sepsis. Gestational age < 37 weeks, not crying immediately at birth, and have received resuscitation at birth were found to be neonatal-related risk factors of neonatal sepsis. Infection prevention strategies need to be strengthening and/or implementing by providing especial attention for the specified determinants.